2018
DOI: 10.22331/q-2018-08-27-87
|View full text |Cite
|
Sign up to set email alerts
|

Almost Quantum Correlations are Inconsistent with Specker's Principle

Abstract: Ernst Specker considered a particular feature of quantum theory to be especially fundamental, namely that pairwise joint measurability of sharp measurements implies their global joint measurability [vimeo.com/52923835 (2009)]. To date, Specker's principle seemed incapable of singling out quantum theory from the space of all general probabilistic theories. In particular, its well-known consequence for experimental statistics, the principle of consistent exclusivity, does not rule out the set of correlations kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…This is, for example, the reading adopted in Ref. [49], where the failure of Specker's principle in any almost quantum theory was demonstrated. On the other hand, we will often also refer to the "joint measurability" of a set of measurement events, by which we mean that this set of measurement events is a subset of the set of measurement outcomes for some choice of measurement setting.…”
Section: Distinguishing Two Consequences Of Specker's Principle: Strumentioning
confidence: 82%
See 2 more Smart Citations
“…This is, for example, the reading adopted in Ref. [49], where the failure of Specker's principle in any almost quantum theory was demonstrated. On the other hand, we will often also refer to the "joint measurability" of a set of measurement events, by which we mean that this set of measurement events is a subset of the set of measurement outcomes for some choice of measurement setting.…”
Section: Distinguishing Two Consequences Of Specker's Principle: Strumentioning
confidence: 82%
“…We know that an almost quantum theory cannot satisfy Specker's principle [49] but it satisfies statistical Specker's principle (or consistent exclusivity). An open question that remains is:…”
Section: Almost Quantum Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Before such a project can be undertaken, however, one needs a better understanding of the scope of joint measurability structures that can be real-ized by quantum systems of limited Hilbert space dimension, particularly if one is keen to build experimental tests and quantum information protocols based on such joint measurability structures. Such an understanding can also potentially aid the elucidation of facts about joint measurability that are particular to quantum theory in the broader landscape of general probabilistic theories [31][32][33][34][35]. Already, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Already, in Ref. [35], it was shown that considering the joint measurability structure corresponding to a complete graph on four vertices is enough to separate almost quantum correlations (generalized to include single laboratory situations) [36,37] from those correlations that can be realized with projective measurements in quantum theory [37]. This result was taken as a failure of Specker's principle [35,38]-that any set of pairwise compatible measurements is globally compatible-for any measurements underlying almost quantum correlations.…”
Section: Introductionmentioning
confidence: 99%